Microbial ureteral stent colonization in renal transplant recipients: frequency and influence on the short-time functional outcome - Bonkat, Gernot; Siegel, Fabian (Transplant infectious disease, 2012)
Abstract: Ureteral stent insertion at the time of renal transplantation significantly decreases complications of urine leakage and obstruction, but bears an intrinsic risk of microbial colonization. Associated urinary tract infection (UTI) may pose a significant risk for graft infection and subsequent graft failure, in particular, during high-level immunosuppression in the early phase after transplantation. The aims of this prospective study were (i) to assess the frequency of microbial ureteral stent colonization (MUSC) in renal transplant recipients by sonication, (ii) to compare the diagnostic value of sonication with that of conventional urine culture (CUC), (iii) to determine biofilm forming organisms, and (iv) to investigate the influence of MUSC on the short-time functional outcome. A total of 80 ureteral stents from 78 renal transplant recipients (deceased donors n = 50, living donors n = 28) were prospectively included in the study. CUC was obtained prior to renal transplantation and at ureteral stent removal. In addition, a new stent sonication technique was performed to dislodge adherent microorganisms. CUCs were positive in 4% of patients. Sonicate-fluid culture significantly increased the yield of microbial growth to 27% (P < 0.001). Most commonly isolated microorganisms by sonication were Enterococcus species (31%), coagulase-negative staphylococci (19%), and Lactobacillus species (19%), microorganisms not commonly observed in UTIs after renal transplantation. The median glomerular filtraton rate (GFR) of the study population increases from 39 mL/min immediately after transplantation (time point A) to 50 mL/min 6 month post transplantation (time point B). In patients without MUSC, the GFR improves from 39 mL/min (A) to 48 mL/min (B) and in patients with MUSC from 39 mL/min (A) to 50 mL/min (B), respectively. In summary, MUSC in renal transplant recipients is common and remains frequently undetected by routine CUC, but colonization had no measurable effect on renal function.